Does prepregnancy weight change have an effect on subsequent pregnancy health outcomes? A systematic review and meta‐analysis. (25th October 2021) - Nagpal, Taniya S.; Souza, Sara C. S.; Moffat, Malcolm; Hayes, Louise; Nuyts, Tinne; Liu, Rebecca H.; Bogaerts, Annick; Dervis, Sheila; Piccinini‐Vallis, Helena; Adamo, Kristi B.; Heslehurst, Nicola
Summary: International guidelines recommend women with an overweight or obese body mass index (BMI) aim to reduce their body weight prior to conception to minimize the risk of adverse perinatal outcomes. Recent systematic reviews have demonstrated that interpregnancy weight gain increases women's risk of developing adverse pregnancy outcomes in their subsequent pregnancy. Interpregnancy weight change studies exclude nulliparous women. This systematic review and meta‐analysis was conducted following MOOSE guidelines and summarizes the evidence of the impact of preconception and interpregnancy weight change on perinatal outcomes for women regardless of parity. Sixty one studies met the inclusion criteria for this review and reported 34 different outcomes. We identified a significantly increased risk of gestational diabetes (OR 1.88, 95% CI 1.66, 2.14, I 2  = 87.8%), hypertensive disorders (OR 1.46 95% CI 1.12, 1.91, I 2  = 94.9%), preeclampsia (OR 1.92 95% CI 1.55, 2.37, I 2  = 93.6%), and large‐for‐gestational‐age (OR 1.36, 95% CI 1.25, 1.49, I 2  = 92.2%) with preconception and interpregnancy weight gain. Interpregnancy weight loss only was significantly associated with increased risk for small‐for‐gestational‐age (OR 1.29 95% CI 1.11, 1.50, I 2  = 89.9%) and preterm birth (OR 1.06 95% CI 1.00, 1.13, I 2  = 22.4%). Our findings illustrate the need for effective preconception and interpregnancy weight management support to improve pregnancy outcomes in subsequent pregnancies.